The effectiveness of organic matter removal in unit processes of the technological groundwater treatment system - Pietrzyk Andżelika; Papciak Dorota (E3S Web of Conferences, 2018)
The study evaluated the content of hydrophobic and hydrophilic organic substances in water subjected to purification in the technological system: coagulation, filtration on anthracite-sand deposits and biofiltration on granular activated carbons. The estimation of the removal efficiency of individual NOM fractions was made on the basis of fractionation method using polymeric resins (DAX-8, XAD-4 and IRA-958). The obtained results allowed to state that the applied water treatment system is effective in removing organic matter and its effectiveness in relation to individual parameters was: 55% for total organic carbon (TOC), 49% for dissolved organic carbon (DOC), 80% for particulate organic carbon (POC), 68% for UV absorbance, 83% for permanganate value and 100% for colour. In the intaken groundwater, the value of the hydrophobic fraction was 84%. The dominant fraction was very hydrophobic acid (VHA), whose content was 4.87 mg C/L (65% DOC). On the grounds of the information on the content of the NOM fraction in the intaken waters, the effectiveness of their removal in the unit processes of the technological system cannot be unequivocally determined. The content of NOM fractions established on the basis of the fractionation procedure and the SUVA parameter does not give explicit results. Further research should be carried out in this respect.